The Role of Nurses in Applying Simplified Physiotherapy Methods - Navruzova Nilufar Orzijonovna; Qurbonova Aziza Alisherovna; Boymurodova Mohinabonu Tursunovna (Лучшие интеллектуальные исследования, 2024)
Physical and pharmacological therapy methods play a significant role in the rehabilitation of patients with severe pain syndrome. At the same time, somatic condition is restored, and compensatory-adaptive processes are stimulated. Physiotherapeutic methods take the lead in achieving anesthesia. In recent years, due to the increasing problems with the musculoskeletal system and neurological issues, pain has become a frequently occurring and difficult-to-relieve syndrome.